Research on a Ground-Based Gas-Liquid Separation Control System Based on Virtual Observation and NMPC - Liao, Haojie; He, Xia; Wang, Peng; Wang, Chuan (Scientific Journal of Technology, 2026)
To address the limitations of conventional technical solutions in surface testing operations for natural gas wells, this study identifies the deficiencies associated with the manual control of gas-liquid separators. A precision pressure control system for surface testing is investigated, integrated with virtual sensing (observation) and Nonlinear Model Predictive Control (NMPC). The mathematical model of a gravity-based gas-liquid separator is introduced, and a virtual observation method based on the Kalman filter is explored. Building upon these foundations, an intelligent control strategy for the separator is developed utilizing NMPC. Experimental results demonstrate that the proposed intelligent control approach, combining virtual sensing with NMPC, significantly enhances control performance and achieves robust stabilization of the gas-liquid separator.